Belize : Use of Fund Resources; Request for Emergency Assistance; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Belize. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The staff report for Belize's use of Fund Resources and Request for Emergency Assistance is examined. Economic growth has been sustained largely by rising oil production, while inflation has remained under control. Despite rising oil production, economic growth has been low in 2007, in part because of the impact of Hurricane Dean. The authorities are confident that the banking system is stable and adequately capitalized, and largely insulated from international market turmoil.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet